2009
DOI: 10.1002/bjs.6679
|View full text |Cite
|
Sign up to set email alerts
|

Development of a virtual reality training curriculum for laparoscopic cholecystectomy

Abstract: This study shows that it is possible to define and develop a whole-procedure VR training curriculum for laparoscopic cholecystectomy using structured scientific methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(168 citation statements)
references
References 19 publications
7
158
0
3
Order By: Relevance
“…Two-handed grasp and cut (transfer) task Hypothesis 3 predicted that the GT group would exhibit superior performance and gaze control on a two-handed transfer test than the DL group, despite both groups exclusively learning on a simpler one-handed task. Generalisation of skills is a vital component of training during the early learning curve phase if video box trainers are to be beneficial for laparoscopic training curricula [14,20,21,24,25]. Both the GT and DL groups improved their completion time in the transfer task from baseline to retention by 46 and 38 %, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-handed grasp and cut (transfer) task Hypothesis 3 predicted that the GT group would exhibit superior performance and gaze control on a two-handed transfer test than the DL group, despite both groups exclusively learning on a simpler one-handed task. Generalisation of skills is a vital component of training during the early learning curve phase if video box trainers are to be beneficial for laparoscopic training curricula [14,20,21,24,25]. Both the GT and DL groups improved their completion time in the transfer task from baseline to retention by 46 and 38 %, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous research has shown that similar two-handed grasping and clipping surgical tasks have been able to differentiate performance between novices and experts; have revealed appropriate construct validity and learning curve progression in novices; and emulate the technical precision required to clip and cut a cystic duct during a laparoscopic cholecystectomy [20,21]. Participants were instructed to complete both tasks as quickly and as accurately as possible.…”
Section: Apparatus and Taskmentioning
confidence: 99%
“…In this study the following three used for assessing surgical performance: (i) number These metrics have been shown to reflect surgical proficiency [16].…”
Section: Evaluation Of Cholecystectomy Performed On Vr Simulatormentioning
confidence: 99%
“…For all considered tasks, the most prominent motion efficiency metrics are time, path length and economy of movements [24,30,31,34]. They are especially important in the tasks which involve touching or grasping objects on the scenario, both with one or two instruments; and that require bi-manual coordination.…”
Section: Clinical Definition Of Metricsmentioning
confidence: 99%
“…However, depending on the nature and difficultness of the task, these metrics might not always show significant differences [57]. For these same tasks, a number of studies have shown that speed of movements can be a differentiating aspect [29,31,48]. This may partly be due to the difficulty of determining an optimal path, which in any case will depend on the task's goal.…”
Section: Clinical Definition Of Metricsmentioning
confidence: 99%